2016
DOI: 10.1371/journal.pone.0157265
|View full text |Cite
|
Sign up to set email alerts
|

Histone Methyltransferase Enhancer of Zeste Homolog 2-Mediated ABCA1 Promoter DNA Methylation Contributes to the Progression of Atherosclerosis

Abstract: ATP-binding cassette transporter A1 (ABCA1) plays a critical role in maintaining cellular cholesterol homeostasis. The purpose of this study is to identify the molecular mechanism(s) underlying ABCA1 epigenetic modification and determine its potential impact on ABCA1 expression in macrophage-derived foam cell formation and atherosclerosis development. DNA methylation induced foam cell formation from macrophages and promoted atherosclerosis in apolipoprotein E-deficient (apoE−/−) mice. Bioinformatics analyses r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 35 publications
1
49
0
1
Order By: Relevance
“…Moreover, we performed RNA sequencing (RNA-seq) analysis to compare the effect of ZRANB1 and EZH2 on global gene expression. A total of 63 genes, including known EZH2 targets or downstream genes SERPINB2 (Kim et al, 2012), PTGS2 (encoding cyclooxygenase-2) (Coward et al, 2014), ABCA1 (Lv et al, 2016), and MMP9 (Delgado-Olguín et al, 2014), were differentially expressed (49 upregulated and 14 downregulated) by at least 1.6-fold (p < 0.05) upon knockdown of either ZRANB1 or EZH2 in LM2 cells (Figures 1G and 1H; Table S1). Taken together, our data suggest that ZRANB1 is a functional regulator of EZH2.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, we performed RNA sequencing (RNA-seq) analysis to compare the effect of ZRANB1 and EZH2 on global gene expression. A total of 63 genes, including known EZH2 targets or downstream genes SERPINB2 (Kim et al, 2012), PTGS2 (encoding cyclooxygenase-2) (Coward et al, 2014), ABCA1 (Lv et al, 2016), and MMP9 (Delgado-Olguín et al, 2014), were differentially expressed (49 upregulated and 14 downregulated) by at least 1.6-fold (p < 0.05) upon knockdown of either ZRANB1 or EZH2 in LM2 cells (Figures 1G and 1H; Table S1). Taken together, our data suggest that ZRANB1 is a functional regulator of EZH2.…”
Section: Resultsmentioning
confidence: 99%
“…4,5 Our laboratory has also demonstrated that maintaining the abundance of ABCA1 protein can effectively ensure RCT and prevent the development of atherosclerosis. [6][7][8] In addition to its role in cholesterol efflux, ABCA1 has recently been considered as an anti-inflammation I nflammation plays important roles in the development of atherosclerosis, the main cause of coronary artery disease (CAD). Accumulation of macrophages into the intima correlates with progression of atherosclerotic plaque and plaque rupture.…”
mentioning
confidence: 99%
“…Ezh2 the methyltransferase corresponding to H3K27 promoted foam cell formation and the development of atherosclerosis in ApoE −/− mice. Mechanistically, Ezh2 induced DNA methyltransferase 1 (Dnmt1) expression, methyl CpG-binding protein-2 (MeCP2) recruitment, and the binding of Dnmt1 and MeCP2 to the ATP-binding cassette transporter A1 (Abca1) promoter, thereby promoting Abca1 gene DNA methylation, which inhibited Abca1 expression and accelerated atherosclerosis [53]. Elevated low-density lipoprotein (LDL) levels are a major risk factor for atherosclerosis development.…”
Section: Histone Methylation In Atherosclerosis and Vascular Intimal mentioning
confidence: 99%